The Influence of Brand Image, Location, Trust and Consumer Satisfaction on The Repurchase Interest of Alfamart Consumers in South Jakarta in 2021 - Novi Lovita Dwi; Elwisam Elwisam; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to analyze the influence of brand image, location, consumer trust and satisfaction on the repurchase interest of Alfamart consumers in South Jakarta in 2021. The sample in this study was 96 respondents using Anderson's formula. This study used primary data with a data collection method through questionnaires distributed to 96 respondents. Data analysis technique using inferential analysis with multiple linear regression and using SPSS program version 23.0. With data testing techniques used in this study include multiple linear regression tests, and research hypothesis testing. From the results of the analysis, it can be concluded that brand image, trust, and consumer satisfaction affect the repurchase interest of Alfamart consumers in Pasar Minggu in 2021. Meanwhile, location does not affect the repurchase interest of Alfamart consumers in South Jakarta in 2021.